Determinant of Return on Assets in Indonesian Islamic Banking - Khodijah Ishak; Muhammad Isa Selamat; Kurniatul Fil Khoirin; Ryan Kurniawan (International Journal of Integrative Sciences, 2023)
This research aims to determine the influence of Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR) on Return On Assets (ROA) of Indonesin Islamic Bank that on the Indonesia Stock Exchange (IDX) during the period of 2015-2017. Th is study financial statements of companies listed on the Indonesia Stock Exchange which were then analyzed using SPSS 23.0 software. The test results show that the Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR) have a significant positive influence on Return On Assets (ROA) and the simultaneous influence between Financing to o Deposit Ratio (FDR), Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) to Return On Assets (ROA) with an R Square value of 0.758. This shows that the percentage of the influence of Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR) to Return On Assets (ROA) simultaneously is 75.8%. While the remaining 24.2% is influenced by other variables outside of this research variable